Musculoskeletal Injury in Reserve Officers' Training Corps: A Report From the Athletic Training Practice-Based Research Network. Issue 9 (23rd September 2020) - Radzak, Kara N.; Sefton, JoEllen M.; Timmons, Mark K.; Lopp, Rachel; Stickley, Christopher D.; Lam, Kenneth C.
Background: Reserve Officers' Training Corps (ROTC) cadets must meet the same physical standards as active duty military servicemembers and undergo organized physical training (PT). ROTC participation, like all physical activity, can result in training-related musculoskeletal injury (MSKI), and of course, cadets could sustain MSKI outside of ROTC. However, MSKI incidence in ROTC programs is largely unknown. Purpose: To describe patient and injury demographics of MSKI in 5 universities' Army ROTC programs. Study Design: Descriptive epidemiology study. Methods: A retrospective chart review of electronic medical records was performed using the Athletic Training Practice-Based Research Network (AT-PBRN). Athletic trainers at 5 clinical practice sites within the AT-PBRN documented injury assessments via a web-based electronic medical record system. Medical records during the 2017-2018 and 2018-2019 academic years were used for analysis. Summary statistics were calculated for age, sex, height, body mass, military science year, training ability group, mechanism of injury, activity type associated with injury, anatomic location of injury, participation status, injury severity, and diagnosis. Results: A total of 364 unique injuries were documented. Cadets in the most advanced fitness group (Alpha; n = 148/364) and in their third year of training (n = 97/364) presented with the most injuries. Injuries most commonly occurred during PT (n = 165/364). Insidious onset (n = 146/364) and noncontact (n = 115/364) mechanisms of injury were prevalent. The most frequent anatomic location of injury was the knee (n = 71/364) followed by the ankle (n = 57/364). General sprain/strain was the most frequent International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code reported (n = 34/364). Conclusion: The knee was the most frequent location of MSKI in ROTC participants, and most MSKIs had insidious onset. Cadets with higher injury frequency were high achieving (Alpha) and in a critical time point in ROTC (military science year 3). The majority of MSKIs can be attributed to ROTC training, with PT being the most frequent activity associated with injury. Civilian health care providers, from whom ROTC cadets will most likely seek medical attention, need to be aware of ROTC physical demands as well as the characteristics of training-related injuries.